Le contrôle gouvernemental des entreprises multinationales : Le cas des États-Unis - Vernon, Ryamond (Études internationales, 1985)
The article is a case study of the relationship between the American government and US multinational corporation. It argues that while the state - MNE relationships vary from country to country, the US pattern is one of a very limited transnational role for government. Main factors in this pattern are the division of powers between the various branches and agencies of the US government, and changes in administrative staff following each national election. Few cases of government effort at business guidance are found: antitrust policy, foreign aid to friend governments, ineffectual protests again nationalisation of foreign subsidiaries of US MNE, exceptional cases of purposeful intervention, and the US adherence to international guide lines to MNE conduct sponsored by OECD. The article studies in more detail the case of oil, in which the US government is supposed to have intervened in a more direct way. The article concludes that US foreign policy is too complex to be understood simply in terms of government support of US multinational abroad. Besides us industry and the American government are themselves too split to produce a single and homogeneous pattern of policy.